Net childcare cost for parents using childcare (Benefits and wages)
This dataset shows the net costs paid by parents for full-time centre-based childcare, after any benefits designed to reduce the gross childcare fees. Childcare benefits can be received in the form of childcare allowances, tax concessions, fee rebates and increases in other benefit entitlements. Data are presented from 2004 onwards